Treatment With Gemfibrozil Prevents the Progression of Chronic Kidney Disease in Obese Dahl Salt-Sensitive Rats - Shields, Corbin A.; Poudel, Bibek; McPherson, Kasi C.; Brown, Andrea K.; Ekperikpe, Ubong S.; Browning, Evan; Sutton, Lamari; Cornelius, Denise C.; Williams, Jan M. (Frontiers in Physiology, 2020)
Recently, we reported that Dahl salt-sensitive leptin receptor mutant (SSLepRmutant) rats exhibit dyslipidemia and renal lipid accumulation independent of hyperglycemia that progresses to chronic kidney disease (CKD). Therefore, in the current study, we examined the effects of gemfibrozil, a lipid-lowering drug (200 mg/kg/day, orally), on the progression of renal injury in SS and SSLepRmutant rats for 4 weeks starting at 12 weeks of age. Plasma triglyceride levels were markedly elevated in the SSLepRmutant strain compared to SS rats (1193±243 and 98±16 mg/day, respectively). Gemfibrozil treatment only reduced plasma triglycerides in the SSLepRmutant strain (410±79 mg/dL). MAP was significantly higher in the SSLepRmutant strain versus SS rats at the end of the study (198±7 vs. 165±7 mmHg, respectively). Administration of gemfibrozil only lowered MAP in SSLepRmutant rats (163±8 mmHg). During the course of the study, proteinuria increased to 125±22 mg/day in SS rats. However, proteinuria did not change in the SSLepRmutant strain and remained near baseline (693±58 mg/day). Interestingly, treatment with gemfibrozil increased the progression of proteinuria by 77% in the SSLepRmutant strain without affecting proteinuria in SS rats. The renal injury in the SSLepRmutant strain progressed to CKD. Moreover, the kidneys from SSLepRmutant rats displayed significant glomerular injury with mesangial expansion and increased renal lipid accumulation and fibrosis compared to SS rats. Treatment with gemfibrozil significantly reduced glomerular injury and lipid accumulation and improved renal function. These data indicate that reducing plasma triglyceride levels with gemfibrozil inhibits hypertension and CKD associated with obesity in SSLepRmutant rats.